(untitled) (Journal of the College of Education for Women, 2019)
Abu Firas al- Hamdani is one of the most prominent abbasid poets Who characterized their poetry with high artistic quality especially in his Romyate which blended the quality of feelings of grief, sorrow, longing and nostalgia that makes sensitive self conflict that stems with time from one hand and with place on the other hand. Because we are dealing with a poet lived west spatial coercive which it has been hurt him within a time conflict swinging between despair and some times patience and hope other times between the present and his painful reality also between the past and the beautiful times.This researcher is to stand on this Romyat by monitoring effectiveness of the poetic text based on conflict between the presence and absence of this dialectic which is and of the important phenomena in the literary text which contribute to the composition and lend it anointed aesthetic through the conflict that exists between its ends. It will focus on three dimensions which represents Romyat essence: the self, time, and place